Hummingbirds - Riggs, Kate. (Amazing animals (Creative Education, Inc. (Mankato, Minn.)), 2014)
"A basic exploration of the appearance, behavior, and habitat of hummingbirds, Earth's smallest birds. Also included is a story from folklore explaining why hummingbirds have beautiful feathers"--